F-18 Labeled Vasoactive Intestinal Peptide Analogue in the PET Imaging of Colon Carcinoma in Nude Mice. (26th December 2013) - Cheng, Dengfeng; Liu, Yuxia; Shen, Hua; Pang, Lifang; Yin, Duanzhi; Wang, Yongxian; Li, Shanqun; Shi, Hongcheng
Abstract : As large amount of vasoactive intestinal peptide (VIP) receptors are expressed in various tumors and VIP-related diseases, radiolabeled VIP provides a potential PET imaging agent for VIP receptor. However, structural modification of VIP is required before being radiolabeled and used for VIP receptor imaging due to its poor in vivo stability. As a VIP analogue, [R 8, 15, 21, L 17 ]-VIP exhibited improved stability and receptor specificity in preliminary studies. In this study, F-18 labeled [ R 8, 15, 21, L 17 ]-VIP was produced with the radiochemical yield being as high as 33.6 % ± 3 % (decay-for-corrected, n = 5 ) achieved within 100 min, a specific activity of 255 GBq/ μ mol, and a radiochemical purity as high as 99% as characterized by radioactive HPLC, TLC, and SDS-Page radioautography. A biodistribution study in normal mice also demonstrated fast elimination of F-18 labeled [ R 8, 15, 21, L 17 ]-VIP in the blood, liver, and gastrointestinal tracts. A further micro-PET imaging study in C26 colon carcinoma bearing mice confirmed the high tumor specificity, with the tumor/muscle radioactivity uptake ratio being as high as 3.03 at 60 min following injection, and no apparent radioactivity concentration in the intestinal tracts. In addition, blocking experiment and Western Blot test further confirmed its potential in PET imaging of VIP receptor-positive tumor.